Quantifiable Bodies: The Influence of Biometric Technologies in Patient Consent - Banville, Morgan; Kalodner-Martin, Elena (Surveillance & Society, 2024)
While research has been done to identify the potential implications of biometric technology on marginalized populations’ privacy and autonomy, this paper contributes to existing research by examining these technologies in healthcare settings. Drawing from insights across surveillance studies, rhetoric of health and medicine, and technical communication, we identify how one leading healthcare institution in New York City has employed rhetorics of efficiency, effectiveness, safety, and security regarding its biometric technology system. This employment of biometric technologies often contributes to patients’ marginalization and dismissal. As we explore, interrogating the language used by the healthcare institution to describe biometrics opens opportunities for us—surveillance studies scholars, patients, allies, students, and more—to ensure that innovations within the healthcare system promote equity, agency, and improved outcomes for all.